Sustained Post-Developmental T-Bet Expression Is Critical for the Maintenance of Type One Innate Lymphoid Cells In Vivo - Schroeder, Jan-Hendrik; Roberts, Luke B.; Meissl, Katrin; Lo, Jonathan W.; Hromadová, Dominika; Hayes, Kelly; Zabinski, Tomasz; Read, Emily; Moreira Heliodoro, Catarina; Reis, Rita; Howard, Jane K.; Grencis, Richard K.; et al. (Frontiers in Immunology, 2021)
Innate lymphoid cells (ILC) play a significant role in the intestinal immune response and T-bet+ CD127+ group 1 cells (ILC1) have been linked to the pathogenesis of human inflammatory bowel disease (IBD). However, the functional importance of ILC1 in the context of an intact adaptive immune response has been controversial. In this report we demonstrate that induced depletion of T-bet using a Rosa26-Cre-ERT2 model resulted in the loss of intestinal ILC1, pointing to a post-developmental requirement of T-bet expression for these cells. In contrast, neither colonic lamina propria (cLP) ILC2 nor cLP ILC3 abundance were altered upon induced deletion of T-bet. Mechanistically, we report that STAT1 or STAT4 are not required for intestinal ILC1 development and maintenance. Mice with induced deletion of T-bet and subsequent loss of ILC1 were protected from the induction of severe colitis in vivo. Hence, this study provides support for the clinical development of an IBD treatment based on ILC1 depletion via targeting T-bet or its downstream transcriptional targets.